2020
DOI: 10.1186/s13020-020-00387-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alkaloids on peripheral neuropathic pain: a review

Abstract: Neuropathic pain is a debilitating pathological pain condition with a great therapeutic challenge in clinical practice. Currently used analgesics produce deleterious side effects. Therefore, it is necessary to investigate alternative medicines for neuropathic pain. Chinese herbal medicines have been widely used in treating intractable pain. Compelling evidence revealed that the bioactive alkaloids of Chinese herbal medicines stand out in developing novel drugs for neuropathic pain due to multiple targets and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 173 publications
0
13
0
Order By: Relevance
“…These findings corroborate with Gouveia et al (2019) , who demonstrated that compounds belonging to the class of terpenes, alkaloids, flavonoids and cannabinoids have been the target of recent studies on their effects on cancer pain. In fact, the analgesic properties of compounds belonging to these classes of natural products have been extensively demonstrated in several studies, due to their ability to modulate neurotransmission systems, inflammatory response and redox imbalance ( Guimarães et al, 2014 ; Gouveia et al, 2018 ; Ferraz et al, 2020 ; Zhu et al, 2020 ; Anand et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…These findings corroborate with Gouveia et al (2019) , who demonstrated that compounds belonging to the class of terpenes, alkaloids, flavonoids and cannabinoids have been the target of recent studies on their effects on cancer pain. In fact, the analgesic properties of compounds belonging to these classes of natural products have been extensively demonstrated in several studies, due to their ability to modulate neurotransmission systems, inflammatory response and redox imbalance ( Guimarães et al, 2014 ; Gouveia et al, 2018 ; Ferraz et al, 2020 ; Zhu et al, 2020 ; Anand et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…These drugs, however, also have some adverse effects, such as drowsiness, edema, ataxia, vertigo, and so on (Onakpoya et al, 2019). Natural alkaloids have a wide range of targets and good efficacy in peripheral neuropathic pain, which provides a new way for natural alkaloids to relieve central neuropathic pain (Zhu et al, 2020).…”
Section: Effects Of Alkaloids On Central Nervous Painmentioning
confidence: 99%
“…For example, indole alkaloids have structural similarities to serotonin, so they are potential sources of anti-depressant drugs [176]. Alkaloids can also impact signal transduction in neurons, and can reduce pain by altering the activity of voltage-gated sodium channels [177]. Other alkaloids intercalate or alkylate DNA, or interfere with protein synthesis or the cytoskeleton, actions that often trigger apoptosis [174].…”
Section: Alkaloidsmentioning
confidence: 99%